sec2A-cosec2A=2sin2A-1/sin2A-cos2A
Attachments:
![](https://hi-static.z-dn.net/files/d17/4b51fea668a107223a0120b8dc6da58c.jpg)
Answers
Answered by
17
Answer:
sec^2 A - cosec^2 A
= 1/cos^2 A - 1/sin^2 A
= sin^2 A-cos^2 A / sin^2 A cos^2 A
= sin^2 A -(1-sin^2 A) / sin^2 A * cos^2 A
= 2sin^2 A - 1 / sin^2 A * cos^2 A
I think there's a mistake in the denominator of the RHS, where it shouldn't be sin^2 A - cos^2 A but it should instead be sin^2 A * cos^2 A
Hope this helps you !
Answered by
1
Answer:
hey mate!!!!!!!!!!!!!!!!!
Attachments:
![](https://hi-static.z-dn.net/files/d6c/1aa6448706ff5c5a5952987a39dcc54e.jpg)
Similar questions